EVALUATION OF DIPHTHERIA SURVEILANCE SYSTEM IN PROBOLINGGO DISTRICT :STUDY OF SYSTEM APPROACH AND ATTRIBUTES - Nur Maulina, Lidya; Shofiya Novita Sari, Siti; Sholikah, Sholikah; Anjar, Retno (Mulawarman International Conference on Tropical Public Health, 2025)
Background : In 2023 there were still deaths due to diphtheria outbreaks in Probolinggo Regency with a CFR (Case Fatality Rate) of 33.33%. Therefore, support is needed through surveillance systems in order to solve different problems. Objective : This study aims to describe the quality of different surveillance systems based on the system approach and surveillance system attributes. Research Methods/ Implementation Methods : This research an evaluation study on the diphtheria surveillance system in 2023 at 17 Puskesmas in the working area of the Probolinggo District Health Office. Respondents were 17 people. Data were collected by interview and document study using questionnaires and check list sheets. Data analysis was conducted by describing the system components and attributes of the surveillance system, and comparing them with the 2023 Diphtheria Control Guidelines, Indonesian Minister of Health Regulation No. 45 of 2014, and surveillance attributes (Guidelines for Evaluation of Public Health Surveillance System) from the CDC. The information obtained is presented in the form of tables and narratives. Results : Evaluation of the diphtheria surveillance system based on inputs, processes, and outputs, namely all respondents (100%) who have a workload of more than one program, officers who attend training (76.47), there are still (41.18%) who have not conducted routine data analysis, and there are still (47.06%) late sending reports, data visualization has not been done (35.29%). While the assessment of surveillance attributes showed that the diphtheria surveillance system is simple, flexible, acceptable, high stability. However, the system is not sensitive, not timely, low positive predictive value because the screening of suspects is still loose and not representative. Conclusion/Lesson Learned : The implementation of the diphtheria surveillance system has mostly been carried out well, supported by the completeness of several surveillance attributes. It is necessary to provide standard operating procedures for recording and reporting, improve coordination with surveillance program holders at Puskesmas to send routine reports on time and optimise the screening of diphtheria suspects.